2013
DOI: 10.4238/2013.september.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen years after the Shahid-Rajaei dam construction: an evaluation of morphometric and genetic differentiation between isolated up- and downstream populations of Capoeta capoeta gracilis (Pisces: Cyprinidae) in the Tajan River of Iran

Abstract: ABSTRACT. We evaluated the effects of the Shahid-Rajaei dam, 14 years after its construction, on morphometric and genetic divergence between up-and downstream populations of the Iranian fish SiahMahi (Capoeta capoeta gracilis). Sixty-six specimens were analyzed. There were significant differences between the 2 groups in the means of 16 morphometric characters (univariate analysis). In discriminant function analysis, the proportion of individuals classified into their original groups was 97 and 100% for up-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Members identified as belonging to this genus are present in all Iranian basins (probably with the exception of southeastern ones), so their global distribution comprises a wide region from Syria, Lebanon, and Turkey in the west to Turkmenistan, Afghanistan, and probably northern Pakistan in the east, Georgia and southwestern Russia in the North, and Iranian shores of Persian Gulf in the south (Bănărescu, ; Coad, ). Recent studies of the genus are mainly taxonomic, including the description of new species (Esmaeili, Zareian, Eagderi, & Alwan, ; Özulug & Freyhof, ; Turan, Kottelat, & Ekmekçi, ; Zareian, Esmaeili, & Freyhof, ), or are ecological, such as evaluations of their value as biomarkers to assess human impact on aquatic environments (Anvarifar et al., , ; Ebrahimi & Taherianfard, ; Fallah, Nematollahi, & Saei‐Dehkordi, ; Faradonbe, Eagderi, & Moradi, ; Johari, Coad, Mazloomi, Kheyri, & Asghari, ; Patimar & Mohammadzadeh, ; Samaee, Patzner, & Mansour, ). Little is known of the genetic variation in extant members of the genus or the diversification patterns that shaped its current diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Members identified as belonging to this genus are present in all Iranian basins (probably with the exception of southeastern ones), so their global distribution comprises a wide region from Syria, Lebanon, and Turkey in the west to Turkmenistan, Afghanistan, and probably northern Pakistan in the east, Georgia and southwestern Russia in the North, and Iranian shores of Persian Gulf in the south (Bănărescu, ; Coad, ). Recent studies of the genus are mainly taxonomic, including the description of new species (Esmaeili, Zareian, Eagderi, & Alwan, ; Özulug & Freyhof, ; Turan, Kottelat, & Ekmekçi, ; Zareian, Esmaeili, & Freyhof, ), or are ecological, such as evaluations of their value as biomarkers to assess human impact on aquatic environments (Anvarifar et al., , ; Ebrahimi & Taherianfard, ; Fallah, Nematollahi, & Saei‐Dehkordi, ; Faradonbe, Eagderi, & Moradi, ; Johari, Coad, Mazloomi, Kheyri, & Asghari, ; Patimar & Mohammadzadeh, ; Samaee, Patzner, & Mansour, ). Little is known of the genetic variation in extant members of the genus or the diversification patterns that shaped its current diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out on the Caspian Sea fishes show that many species possess speciation and population formation microprocess running, as the Black Sea species (Gholiev 1997). There are several reports on the southern Caspian Sea fishes (e.g., Abdolhay et al 2010;AnvariFar et al 2011AnvariFar et al , 2013 which indicate the existence of morphological variability in different parts of this basin. However, information on population variability and differentiation of Caspian lamprey in the southern Caspian Sea basin is still rather limited.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean circulation acts as a barrier to the dispersal of larvae and leads to genetic structuring (Karlsson et al, 2009;Castillo-Olguín et al, 2012;Prieto-Ríos et al, 2014) and morphological differentiation (AnvariFar et al, 2013;Gkafas et al, 2013). The morphological variability recorded among different localities or geographic variants may be due to the genetic structure or to differences in the environmental conditions that prevail in each geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of morphological differences among populations are often difficult to explain (Poulet et al, 2004;Silva et al, 2008). It has been suggested that the morphological characteristics of fish are determined by the interaction between genetic and environmental factors (Poulet et al, 2004;Salini et al, 2004;Pinheiro et al, 2005;AnvariFar et al, 2011AnvariFar et al, , 2013. Studies such as that of Pinheiro et al (2005) make clear that the environmental characteristics that prevail during the early stages of development, when individuals may be phenotypically affected by the environment, are particularly important regarding morphological results.…”
Section: Discussionmentioning
confidence: 99%